2003
DOI: 10.1128/mcb.23.1.272-279.2003
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic Antigen-Related Cell Adhesion Molecule 10 Expressed Specifically Early in Pregnancy in the Decidua Is Dispensable for Normal Murine Development

Abstract: The carcinoembryonic antigen (CEA) family consists of a large group of evolutionarily and structurally divergent glycoproteins. The murine CEACAM9 and CEACAM11-related proteins as well as the pregnancyspecific glycoproteins (PSG) are secreted members of the CEA family which are differentially expressed in fetal trophoblast cell populations during placental development. PSG are essential for a successful pregnancy, possibly by protecting the semiallotypic fetus from the maternal immune system. In contrast, Ceac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…(Fig. 5B) may arise from the maternal decidua as suggested in the study by Finkenzeller et al [33]. This finding, together with the lack of an RNA message in embryo samples at 4.5 and 10.5-18.5 d.p.c.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…(Fig. 5B) may arise from the maternal decidua as suggested in the study by Finkenzeller et al [33]. This finding, together with the lack of an RNA message in embryo samples at 4.5 and 10.5-18.5 d.p.c.…”
Section: Discussionsupporting
confidence: 56%
“…On ejaculation, the CEACAM10-sperm binding may take place in the semen to enhance sperm motility. Finkenzeller et al [33] demonstrated that Ceacam10 Ϫ/Ϫ male and female mice developed indistinguishably from wild-type litter mates with respect to sex ratio, weight gain, and fertility, but a significant reduction by 23% of litter size was observed in Ceacam10 Ϫ/Ϫ mating. Although this may be partially attributed to the lack of CEACAM10 in the semen of Ceacam10-inactivated males, it remains arguable whether in vitro CEACAM10-enhanced sperm motility may play a significant role after coitus under natural circumstances.…”
Section: Discussionmentioning
confidence: 96%
“…To investigate this possibility further, we analysed the expression profile of Psg genes in the giant cells and spongiotrophoblast using quantitative methods. The earliest that Psg transcripts have been detected in the murine placenta is E6.5 in trophoblast giant cells (Finkenzeller et al 2003). It is difficult to isolate cDNA from specific embryonic tissues at this stage, so our analysis began at E8.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there was generally good agreement between the two methods of expression analysis we cannot determine, based on current data, whether Psg gene expression differences reflect selection for divergent functions, or increased gene dosage for enhancement of an existing function, because expression levels were uniformly low for many family members, and there was a general trend of increased expression during gestation. Psg transcripts are found from day 6.5 of embryonic development onward in primary trophoblast giant cells, later (from day 10.5) in spongiotrophoblast cells and, to a lesser extent, in a cell population in the deciduas basalis at day 14.5 [40]. At present, it is unclear whether the various Psg genes exhibit different cellular expression patterns, which might indicate divergent functions of the various PSGs.…”
Section: Discussionmentioning
confidence: 99%